Lyme disease overdiagnosis in a large healthcare system: a population-based, retrospective study. (October 2019) - Webber, B.J.; Burganowski, R.P.; Colton, L.; Escobar, J.D.; Pathak, S.R.; Gambino-Shirley, K.J.
Abstract: Objectives: To evaluate the impact of false-positive IgM immunoblots on Lyme disease treatment and case reporting in a large healthcare system. Methods: We obtained the results of all Lyme disease serological tests ordered at U.S. Air Force healthcare facilities in the USA between January 2013 and December 2017. We conducted chart reviews to adjudicate positive IgM immunoblots (from two-tier and independent testing) as true positives or false positives using established criteria, and we assessed whether these cases were reported to the U.S. Department of Defense surveillance system. Results: Of the 18 410 serum tests (17 058 immunoassays and 1352 immunoblots) performed on 15 928 unique individuals, 249/1352 (18.4%) IgM immunoblots were positive. After excluding repeat tests, insufficiently documented cases, and participants with a history of Lyme disease, 212 positive IgM immunoblot cases were assessed. A total of 113/212 (53.3%) were determined to be false positives. Antibiotics were prescribed for Lyme disease for 97/99 (98.0%) participants with a true-positive test and 91/113 (80.5%) participants with a false-positive test. The number of false-positive cases reported to the surveillance system was identical to the number of unreported true-positive cases ( n  = 44). Conclusions: Lyme disease serological tests were overused in a large healthcare system, and positive results were frequently misinterpreted, leading to misdiagnosis and widespread antibiotic misuse. Underreporting of true-positive cases was offset by overreporting of false-positive cases, suggesting that the discrepancy between the reported incidence and true incidence of Lyme disease may not be as significant as previously assumed.